Cover Feature: Porphycene Protonation: A Fast and Reversible Reaction Enabling Optical Transduction for Acid Sensing (ChemPhotoChem 11/2020). Issue 11 (29th October 2020) - Bossi, Alberto; Waluk, Jacek; Yivlialin, Rossella; Penconi, Marta; Campione, Marcello; Bussetti, Gianlorenzo
Abstract : The Cover Feature depicts the effective color change, from blue to green, of a porphycene film once exposed to acid vapors. In their broad concept, "HCl" branded glasses and optometric tables evidence the set of spectroscopic techniques, such as absorption, emission and surface differential reflectivity, employed in this study (graphics and concepts by Elisabetta Borseti). More information can be found in the Article by Alberto Bossi and co‐workers .